Expulsion analysis of resistance spot welding on zinc-coated steel by detection of structure-borne acoustic emission signals. Issue 9 (June 2016) - Yi, Luo; Rui, Wan; Xiaojian, Xie; Yang, Zhu
Abstract According to the structure-borne acoustic emission (AE) signals detected in resistance spot welding (RSW) on zinc-coated steel, the main inducing factors of expulsion were analyzed by the mathematical method of orthogonal experimental design (OED) and the analysis of variance (ANOVA) technique. The AE signals of expulsion were used to assess the effect of expulsion on the overload performance of spot welds. The results showed that the expulsion can be analyzed by the waveform of AE signals detected in welding process. The most important factor to induce expulsion was welding current, and the second important factor was electrode pressure. The importance of welding time and the matching of welding current-electrode pressure were close to induce expulsion. An overlarge welding current induced heavy expulsion, which also reduced the strength of spot weld significantly. But, a small expulsion will not significantly affect the strength of spot weld, which made it acceptable to some extent.